Sous Vide Cookery: Foodservice Application for Larger, Less Tender Cuts - Chad Carr; Derek Griffing; Kaylie Madore; Dwain Johnson; Jason Scheffler; João Neto (EDIS)
Meat with an abundance of connective tissue presents a certain challenge to cooks who want to make it more tender while still properly eliminating pathogens that cause foodborne illness. Sous vide cookery provides precise temperature control and tenderness improvement with minimal supervision throughout cooking as well as consistent, almost perfect reproducibility. This 4-page fact sheet introduces the reader to the sous vide method and covers its advantages and necessary equipment. The piece also offers tips on cooking, chilling, storing, and reheating large cuts of meat. Written by Chad Carr, Derek Griffing, Kaylie Madore, Dwain Johnson, Jason Scheffler, and João Neto, and published by the UF Department of Animal Sciences, September 2015.